ZONAL LABELING OF EDGE COMB PRODUCT OF GRAPHS - Soewongsono, Junita Christine; Putra, Ganesha Lapenangga; Ariyanto, Ariyanto; Pangaribuan, Rapmaida Megawaty (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2024)
Given a plane graph G=(V,E). A zonal labeling of graph G is defined as an assignment of the two nonzero elements of the ring Z_3, which are 1 and 2, to the vertices of G such that the sum of the labels of the vertices on the border of each region of the graph is 0Z_3. A graph G that possess such a labeling is termed as zonal graph. This paper will characterize edge comb product graphs that are zonal. The results show that P_m_eC_n, C_n_e C_r, S_p_e C_n, and S_p_e F_t are zonal in some cases, but not in others.